Pembelajaran Kaligrafi di Pondok Pesantren Sirajul Huda: Analisis Perkembangan dan Tantangan - Nashfati, Nabila; Br. Karo, Tri Lasti; Nasution, Sahkholid (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Calligraphy learning at Sirajul Huda Islamic Boarding School is an integral part of Islamic religious education that aims to develop artistic skills while strengthening spiritual values. This study uses a qualitative approach to analyze the development of calligraphy learning, the challenges faced, and opportunities that can be utilized to improve the quality of teaching. The methods applied at the Islamic boarding school combine traditional techniques with modern technology, and involve collaboration between Islamic boarding school managers, teachers, and the calligraphy art community. The results of the study indicate that despite challenges such as time constraints and variations in student abilities, the program has developed positively with the support of adequate facilities, competitions, and teacher training. Government support and collaboration with the calligraphy art community were also identified as important factors in strengthening the quality of learning. Sirajul Huda Islamic Boarding School has the potential to become a center of excellence for Islamic calligraphy learning by integrating art, spirituality, and technology.